UNS N10003 alloy surface carburizing method

By gas carburizing the surface of UNS N10003 alloy, the carbon content and carbide quantity are improved, and the problem of insufficient friction and wear resistance of the alloy in high-temperature molten salt environment is solved, and significant hardness improvement and high-temperature performance improvement are achieved.

CN113373401BActive Publication Date: 2025-04-01SHANGHAI INSTITUTE OF APPLIED PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202010116111.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-02-25
Publication Date
2025-04-01
Estimated Expiration
2040-02-25

AI Technical Summary

Technical Problem

Hastelloy N alloy is prone to pump jamming in high temperature molten salt environments, resulting in insufficient friction and wear resistance and cannot meet the needs of components such as under-liquid bearings and valves.

Method used

By gas carburizing the surface of UNS N10003 alloy, the carbon potential is adjusted between 0.6 and 0.9%, and the heat is insulated for 2 to 72 hours, the carbon content and the amount of M6C type carbide in the alloy are increased, thereby improving the surface hardness.

Benefits of technology

It significantly improves the hardness of the surface of UNS N10003 alloy, and the hardness layer can reach more than 100μm, effectively improving its high-temperature friction and wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113373401B_ABST
    Figure CN113373401B_ABST
Patent Text Reader

Abstract

The present application relates to surface treatment technology, and discloses a method for carburizing the surface of a UNS N10003 alloy. The method comprises: placing the UNS N10003 alloy in a gas carburizing furnace; raising the furnace temperature to 910-980°C and then keeping the temperature for 2-72 hours, during which a carbon-containing gas is introduced to adjust the carbon potential to between 0.6% and 0.9%, and then performing carburizing treatment. The embodiments of the present application can effectively improve the surface hardness of the UNS N10003 alloy, thereby improving its friction and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a surface treatment technology, and in particular to a surface carburizing technology for a UNS N10003 alloy. Background Art

[0002] The operating temperature of molten salt (fluoride salt or chloride salt) can be above 700℃. It is an excellent heat transfer and heat storage medium, which can greatly improve the working efficiency of high-temperature energy equipment, such as solar thermal collectors or molten salt reactors. In the 1960s, in order to meet the needs of molten salt reactors, the Oak Ridge National Laboratory in the United States developed Hastelloy N (UNS N10003) alloy. The alloy has high strength, good plasticity and toughness, good machinability, good tolerance to neutron radiation, better high-temperature strength than iron-based alloys, and excellent corrosion resistance in high-temperature molten salts. It has been successfully used in reactor vessels, loop pipes, heat exchangers and other parts.

[0003] Since the hardness of Hastelloy N alloy is relatively low, only about 180HV, the molten salt pump made of it is prone to pump jamming. Therefore, Oak Ridge National Laboratory tried to improve the wear resistance of Hastelloy N alloy in the 1960s. There are two specific technical routes: one of which is to spray / surface hard coating on the surface of UNS N10003 alloy to improve its friction and wear resistance. Oak Ridge began to study hard coatings during the ANP project in the 1950s and proposed 6 suitable cemented carbide combinations, but with the end of the ANP project, this work also came to a temporary end. With the proposal of the MSBR project in the 1960s, long-axis pumps have been paid attention to again. Since 1967, Oak Ridge has restarted the selection of submerged bearing materials. Through thermal cycle analysis, Linde LW-5 (25% WC+W-Cr caribies+7% Ni) was finally selected. Unfortunately, with the interruption of the MSBR project, the relevant work on submerged bearings has also stopped. Another technical route is to perform carburizing treatment on the surface of UNS N10003 alloy. According to the literature (Asle Trans, 4 (1961) 263-274.), the number of pump jams of submerged bearings made of carburized Hastelloy N alloy is significantly less than that of uncarburized Hastelloy N alloy. Unfortunately, it only describes the heat treatment of Hastelloy N alloy wrapped with carbon bricks, and does not provide specific carburizing process parameters and the microstructure and mechanical properties data of Hastelloy N alloy itself after carburization. Since the MSRE project finally adopted the cantilever pump as the final design solution, the research on carburized Hastelloy N alloy was terminated.

[0004] Since the submersible bearings, valves and other components of molten salt reactors and solar thermal collectors require materials to be resistant to friction and wear in high-temperature molten salt environments, there is an urgent need to increase the surface hardness of UNS N10003 alloy to improve its friction and wear resistance. Summary of the invention

[0005] The purpose of the present application is to provide a method for carburizing the surface of UNS N10003 alloy, which can effectively improve the surface hardness of UNS N10003 alloy and thus improve its high temperature friction and wear resistance.

[0006] The present application discloses a method for carburizing the surface of a UNS N10003 alloy, comprising:

[0007] The UNS N10003 alloy is placed in a gas carburizing furnace;

[0008] The furnace temperature is raised to 910-980°C and then kept warm for 2-72 hours. During the warming period, carbon-containing gas is introduced to adjust the carbon potential between 0.6% and 0.9% for carburizing treatment.

[0009] In a preferred embodiment, the furnace temperature is raised to 910-980° C. and then kept at this temperature for 2-72 hours. During the holding period, carbon-containing gas is introduced to adjust the carbon potential to between 0.6% and 0.9% for carburizing treatment, further comprising:

[0010] The furnace temperature is raised to 940±5° C. and then kept at this temperature for 22 to 48 hours. During the keeping temperature period, carbon-containing gas is introduced to adjust the carbon potential between 0.7 and 0.75% to perform carburizing treatment.

[0011] In a preferred embodiment, after the carburizing treatment, the method further comprises:

[0012] The carburized UNS N10003 alloy is furnace cooled or air cooled.

[0013] In a preferred embodiment, after the carburized UNS N10003 alloy is furnace cooled or air cooled, the method further comprises:

[0014] After furnace cooling or air cooling, keep UNS N10003 at 650-750℃ for more than 500h.

[0015] In a preferred embodiment, the step of keeping the furnace-cooled or air-cooled UNS N10003 at 650-750° C. for more than 500 hours further comprises:

[0016] Keep the furnace cooled or air cooled UNS N10003 at 700±5℃ for more than 500h.

[0017] In a preferred embodiment, the step of keeping the furnace-cooled or air-cooled UNS N10003 at 700±5°C for more than 500 hours further comprises:

[0018] Keep the furnace-cooled or air-cooled UNS N10003 at 700±5℃ for 500h.

[0019] In a preferred embodiment, the carbon-containing gas is one of the following gases or a mixture of the following gases:

[0020] Methanol, propane, carbon dioxide, acetylene.

[0021] In the implementation manner of the present application, at least the following advantages and effects are included:

[0022] UNS N10003 alloy is a nickel-based solid solution strengthened alloy (Ni-16Mo-7Cr) with high Mo and low Cr, and its carbon mass percentage is 0.04-0.08%. Figure 5 The present invention is a curve diagram of the type and quantity of carbides of UNS N10003 alloy as the carbon content changes (calculated using the TTNi-8 database of JMatPro 7.0 software). Within this carbon content range, the percentage of carbides in the matrix is ​​3-4wt.%. The present invention can increase the carbon content in the alloy by gas carburizing the UNS N10003 alloy, thereby increasing the number of M6C type carbides and further increasing the hardness of the alloy surface. Since the solid solubility of carbon in nickel-based alloys is usually no more than 0.2wt.% (Corrosion, 56 (2000) 801-808.), during carburizing, the alloy is kept at 910-980°C for 2-72h, and carbon-containing gas is introduced and the carbon potential is adjusted between 0.6% and 0.9%. The carburizing treatment can increase the percentage of carbides to 10wt.%. It is verified through experiments that the carburizing treatment based on the carburizing parameters can make the surface hardness of UNS N10003 alloy reach above 300HV, and the hardness layer above 260HV can reach above 100μm, which effectively improves its high temperature friction and wear resistance.

[0023] Furthermore, during carburizing treatment, the temperature is set to 940±5°C, the carbon potential is 0.7-0.75%, and the carburizing time is 22-48h, so that the alloy after carburizing has the highest hardness, the thickness of the effective carburized layer is the largest, the carburizing effect is the best, and its high-temperature friction and wear resistance is the best.

[0024] Furthermore, after carburizing, the UNS N10003 is placed in a heat treatment furnace, for example, at 650-750° C. for more than 500 hours for heat treatment, followed by furnace cooling or air cooling. This can further promote the diffusion of unreacted carbon dissolved on the surface of the alloy into the interior of the alloy, increase the amount of carbides in the alloy, and thus further increase the thickness of the carburized layer to 1000 μm.

[0025] A large number of technical features are recorded in the specification of this application, which are distributed in various technical solutions. If all possible combinations of technical features of this application (i.e., technical solutions) are to be listed, the specification will be too long. In order to avoid this problem, the various technical features disclosed in the above-mentioned invention content of this application, the various technical features disclosed in the various embodiments and examples below, and the various technical features disclosed in the accompanying drawings can be freely combined with each other to form various new technical solutions (these technical solutions are all deemed to have been recorded in this specification), unless the combination of such technical features is technically infeasible. For example, in one example, feature A+B+C is disclosed, and in another example, feature A+B+D+E is disclosed, and features C and D are equivalent technical means that play the same role. Technically, only one can be used, and it is impossible to use them at the same time. Feature E can be combined with feature C technically. Then, the solution of A+B+C+D should not be deemed to have been recorded because it is technically infeasible, and the solution of A+B+C+E should be deemed to have been recorded. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic flow chart of a method for carburizing the surface of a UNS N10003 alloy according to the first embodiment of the present application;

[0027] Figure 2 It is the surface hardness distribution curve of UNS N10003 after carburization according to Examples 1 to 5 of the present application. ;

[0028] Figure 3 It is a schematic diagram of the metallographic structure of the non-carburized UNS N10003 alloy Examples 2 to 4 according to the present application at a distance of 50 μm from the alloy surface;

[0029] Figure 4 is the surface hardness distribution curve of UNS N10003 after carburization according to Examples 2, 6 to 8 of the present application;

[0030] Figure 5 This is a curve chart showing the type and quantity of carbides in UNS N10003 alloy as its carbon content changes. DETAILED DESCRIPTION

[0031] In the following description, many technical details are provided to help readers better understand the present application. However, those skilled in the art can understand that the technical solution claimed in the present application can be implemented even without these technical details and various changes and modifications based on the following embodiments.

[0032] Description of some concepts:

[0033] Carbon potential: carbon potential. Carbon potential is the same as water potential and electric potential. The potential difference determines the trend of material flow. The carbon potential difference determines the direction of carbon diffusion. When freely diffusing, carbon always diffuses from places with high carbon potential to places with low carbon potential.

[0034] In order to make the objectives, technical solutions and advantages of the present application clearer, the implementation methods of the present application will be further described in detail below in conjunction with the accompanying drawings.

[0035] The first embodiment of the present application relates to a method for carburizing the surface of a UNS N10003 alloy, the process of which is as follows: Figure 1 As shown, the method comprises the following steps:

[0036] In step 101, UNS N10003 alloy is placed in a gas carburizing furnace.

[0037] For example, UNS N10003 alloy may be loaded into a graphite boat and placed in a gas carburizing furnace.

[0038] Then, enter step 102, raise the furnace temperature to 910-980°C and keep it at this temperature for 2-72 hours. During the keeping temperature period, introduce carbon-containing gas to adjust the carbon potential between 0.6% and 0.9% to perform carburizing treatment. For example, the furnace temperature can be raised to 910°C and then kept warm for 2h, 48h or 72h. During the insulation period, carbon-containing gas is introduced to adjust the carbon potential at 0.6%, 0.7% or 0.9% for carburizing treatment; for another example, the furnace temperature can be raised to 940°C and then kept warm for 2h, 48h or 72h. During the insulation period, carbon-containing gas is introduced to adjust the carbon potential at 0.6%, 0.7% or 0.9% for carburizing treatment; for another example, the furnace temperature can be raised to 980°C and then kept warm for 2h, 48h or 72h. During the insulation period, carbon-containing gas is introduced to adjust the carbon potential at 0.6%, 0.7% or 0.9% for carburizing treatment; and it is not limited to this, any combination contained in the range is within the scope of protection of the present application. This makes the surface hardness of UNS N10003 after carburization exceed 300HV. Taking 260HV as the hardness standard of the effective carburized layer (hardness increased by 50%), the effective carburized layer reaches 100μm.

[0039] In a preferred embodiment, step 102 may further include the following steps:

[0040] The furnace temperature is raised to 940±5℃ and then kept warm for 22 to 48 hours. During the insulation period, carbon-containing gas is introduced to adjust the carbon potential between 0.7 and 0.75% for carburizing. For example, the furnace temperature can be raised to 940℃ and then kept warm for 22 hours, 35 hours or 48 hours. During the insulation period, carbon-containing gas is introduced to adjust the carbon potential to 0.7%, 0.725% or 0.75% for carburizing; and it is not limited to this, any combination included in the range is within the protection scope of this application. Under this condition, the alloy hardness after carburizing is the highest, the thickness of the effective carburized layer is the largest, the carburizing effect is the best, and its high-temperature friction and wear resistance is the best.

[0041] The method of adjusting the carbon potential includes but is not limited to adjusting the carbon potential by adjusting the partial pressure of the gas.

[0042] Optionally, after step 102, the following steps are also included:

[0043] The carburized UNS N10003 alloy is furnace cooled or air cooled.

[0044] Among them, after heating, the temperature needs to be cooled down. Controlled cooling in the heating furnace is called furnace cooling; cooling in the air is called air cooling.

[0045] Optionally, after the above “cooling the carburized UNS N10003 alloy in a furnace or in air”, the following steps are also included:

[0046] After furnace cooling or air cooling, the UNS N10003 is kept at 650-750°C for more than 500 hours for heat treatment. For example, the heat treatment can be carried out at 650°C for 500 hours, 800 hours or 1000 hours; for another example, the heat treatment can be carried out at 700°C for 500 hours, 800 hours or 1000 hours; for another example, the heat treatment can be carried out at 750°C for 500 hours, 800 hours or 1000 hours; and without limitation, any combination included in the scope is within the protection scope of this application.

[0047] It should be noted that: since the M6C carbide in UNS N10003 alloy has poor stability above 750℃ and will redissolve into the alloy matrix, the heat treatment temperature after carburizing should not exceed 750℃. Moreover, compared with the original sample without aging, the hardness change is not obvious when the aging time is less than 500h, while the thickness of the effective carburized layer increases significantly after aging for 500h, reaching 1000μm. This is because the diffusion of carbon takes time. When the aging time is short (for example, 100h), the carbon atoms on the surface cannot diffuse into the alloy, and the hardening effect is not obvious.

[0048] Preferably, the above-mentioned “keeping the UNS N10003 after furnace cooling or air cooling at a temperature of 650-750° C. for more than 500 hours” may further include the following steps:

[0049] After furnace cooling or air cooling, the UNS N10003 is kept at 700±5℃ for more than 500h for heat treatment.

[0050] In a preferred embodiment, the above “keeping the UNS N10003 after furnace cooling or air cooling at 700±5℃ for more than 500h” further includes:

[0051] Keep the furnace-cooled or air-cooled UNS N10003 at 700±5℃ for 500h.

[0052] There are many types of carbon-containing gases involved in this embodiment. For example, the carbon-containing gas is one of the following gases or a mixture of the following gases: methanol, propane, carbon dioxide, acetylene. And it is not limited to this, all existing and to be developed carbon-containing gases that can be used for gas carburizing can be used in this application.

[0053] Optionally, the mass percentage composition of the UNS N10003 alloy is: 15.0-18.0% Mo, 6.0-8.0% Cr, 0-5.0% Fe, 0-1.0% Mn, 0-1.0% Si, 0-0.5% Al+Ti, 0.04-0.08% C, 0-0.2% Co, 0-0.5% W, 0-0.5% V, 0-0.015% P, 0-0.002% S, 0-0.35% Cu, 0-0.01% B, and the rest is Ni (according to ASME BPVCII-B 2019p601).

[0054] In order to better understand the technical solution of the present application, a set of example experiments according to the first embodiment of the present application is described below, and the details listed in the example experiments are mainly for ease of understanding and are not intended to limit the scope of protection of the present application. The composition of the UNS N10003 alloy used in the example experiments is shown in Table 1. The example experiments include Examples 1 to 8.

[0055] In Examples 1 to 8, the UNS N10003 alloy is first loaded into a gas carburizing furnace; then a mixed gas of methanol (CH3OH) and propane (C3H8) is introduced into the carburizing furnace, and the surface of the UNSN10003 alloy is carburized according to different carburizing process parameters shown in Table 2; after carburizing, the alloy is cooled with the furnace temperature; after cooling with the furnace temperature, only Examples 6 to 8 are heat treated as shown in Table 2.

[0056] Table 1

[0057] Ni Mo Cr Fe Mn Si Al Ti C Bal. 16.2% 7.2% 3.9% 0.5% 0.3% 0.3% 0.01% 0.05%

[0058] Table 2

[0059] temperature Carbon Potential (CP) Carburizing time Heat treatment after carburizing Example 1 910℃ 0.90% 2h none Example 2 940℃ 0.70% 22h none Example 3 940℃ 0.75% 48h none Example 4 940℃ 0.75% 72h none Example 5 980℃ 0.60% 2h none Example 6 940℃ 0.70% 22h 700℃100h Example 7 940℃ 0.70% 22h 700℃500h Example 8 940℃ 0.70% 22h 700℃1000h

[0060] like Figure 2 The surface hardness distribution curves of UNS N10003 after carburization in Examples 1 to 5 are shown. Figure 2 It can be seen that the surface hardness of UNS N10003 after carburization in Examples 1 to 5 exceeds 300HV. Taking 260HV as the hardness standard of the effective carburized layer (the hardness is increased by 50%), the effective carburized layer reaches 100μm. Figure 2 It can also be seen that for Examples 2 to 3, under the carburizing parameters of 940°C carburizing temperature, 0.7% to 0.75% carbon potential, and 22 to 48h carburizing time, the surface hardness of UNS N10003 after carburizing is the highest, the thickness of the effective carburized layer is the largest, and the carburizing effect is the best.

[0061] like Figure 3 The uncarburized UNS N10003 alloy (corresponding to Figure 3 (a) Examples 2 to 4 (corresponding to Figure 3 Schematic diagram of the metallographic structure at 50 μm from the alloy surface (b) to (d). Figure 3 It can be seen that there are only some grain boundary carbides in the uncarburized UNS N10003 alloy, but after carburizing for 22 to 48 hours, the number of carbides increases significantly with time, and the size of carbides decreases, which is equivalent to carbides dispersing and strengthening the alloy matrix, which is beneficial to the improvement of hardness. After 72 hours of carburizing, the number of carbides decreases, while the size increases significantly, and the hardness decreases accordingly.

[0062] Examples 6 to 8 are samples of UNS N10003 alloy that were carburized at 940° C. for 22 hours and then aged at 700° C. for 100 hours, 500 hours, and 1000 hours, respectively.

[0063] like Figure 4 The surface hardness distribution curves of UNS N10003 after carburization in Example 2 and Examples 6 to 8 are shown. Figure 4 It can be seen that the hardness of the samples aged for 100 hours after carburizing and those not aged after carburizing has no significant change, while the thickness of the effective carburized layer increases significantly after aging for 500 hours after carburizing, reaching 1000μm. This is because the diffusion of carbon takes time. When the aging time is short (for example, 100 hours), the carbon atoms on the surface cannot diffuse into the alloy, and the hardening effect is not obvious.

[0064] It should be noted that in the application documents of this patent, relational terms such as first and second are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "including one" do not exclude the existence of other identical elements in the process, method, article or device including the elements. In the application documents of this patent, if it is mentioned that an action is performed according to an element, it means that the action is performed at least according to the element, which includes two situations: performing the action only according to the element, and performing the action according to the element and other elements. Expressions such as multiple, multiple, and multiple include 2, 2 times, 2 kinds, and more than 2, more than 2 times, and more than 2 kinds. Furthermore, the numerical ranges contained in this application include “~” and “—”, which include the values ​​at both ends of the range.

[0065] All documents mentioned in this application are considered to be included in the disclosure of this application as a whole, so that they can be used as the basis for modification when necessary. In addition, it should be understood that after reading the above disclosure of this application, those skilled in the art can make various changes or modifications to this application, and these equivalent forms also fall within the scope of protection claimed in this application.

Claims

1. A method for carburizing the surface of UNS N10003 alloy, characterized in that: include: The UNS N10003 alloy is placed in a gas carburizing furnace; Raise the furnace temperature to 940±5℃ and keep it warm for 22 to 48 hours. During the warming period, introduce carbon-containing gas to adjust the carbon potential between 0.7 and 0.75% for carburizing treatment; The carburized UNS N10003 alloy is furnace cooled or air cooled; The furnace cooled or air cooled UNS N10003 is kept at 650-750°C for 500-1000 hours.

2. The method for carburizing the surface of UNS N10003 alloy according to claim 1, characterized in that: The step of keeping the furnace-cooled or air-cooled UNS N10003 at 650-750° C. for 500-1000 hours further comprises: Keep the furnace-cooled or air-cooled UNS N10003 at 700±5℃ for 500-1000 hours.

3. The method for carburizing the surface of UNS N10003 alloy as claimed in claim 2, characterized in that: The step of keeping the furnace-cooled or air-cooled UNS N10003 at 700±5° C. for 500-1000 hours further comprises: After furnace cooling or air cooling, keep UNS N10003 at 700±5℃ for 500 hours.

4. The method for carburizing the surface of UNS N10003 alloy according to claim 1, characterized in that: The carbon-containing gas is one of the following gases or a mixture of the following gases: Methanol, propane, carbon dioxide, acetylene.

Citation Information

Patent Citations

  • Process to strengthen the grain boundaries of a component made from a Ni based superalloy

    EP1078996A1